Pengaruh Leader Member Exchange Terhadap Kinerja Pegawai - Hambali, Dewi Rahayu; Setiawardani, Maya (Jurnal Riset Bisnis dan Investasi, 2015)
Leaders have the responsibility for managing their human resources. Thus, a good relationship between leaders and their subordinates is needed in order to support the achievement of organizational goals. But in reality, indirectly leaders give higher trust and respect to some of their subordinates. Therefore, the performance of each employee would not be equal to each other. During four semesters of 2013-2014, there has been a fluctuation of the results of the measurement of employee performance of PT PLN (Persero) Distribusi Jawa Barat dan Banten. The decrease in employee performance began to occur in the second semester of 2013, and the more significant decrease occurred in the second semester of 2014. Of course, this performance’s decreasing would give negative impacts for the company. Based on these problems, this study was conducted to determine how the influence of leader-member exchange on employee performance at Distribution Office of PT PLN (Persero) Distribusi Jawa Barat dan Banten. Simple random sampling technique was used to collect data through questionnaires distributed to 123 respondents who are functional employees at the Distribution Office of PT PLN (Persero) Distribusi Jawa Barat dan Banten. The analysis method used in this research is the classical assumption test, descriptive analysis, correlation, simple linear regression and hypothesis testing with SPSS 20. The results showed that Distribution Office of PT PLN (Persero) Distribusi Jawa Barat dan Banten has a high leader-member exchange and good performance. There is a moderate correlation between leader-member exchange and employee performance. Leader-member exchange contributes positively and significantly affect their employee performance of 23,7% while the remaining 76,3% is affected by other factors contribution that is not explained in this research.